What Are the Participants' Perspectives of Taking Melatonin for the Treatment of Nocturia in Multiple Sclerosis? A Qualitative Study Embedded within a Double-Blind RCT. (18th October 2018) - Khan, Rafiyah; Uren, Alan; Canham, Luke; Cottrell, David; Drake, Marcus J.; Cotterill, Nikki
Abstract : Background . Multiple Sclerosis (MS) is a chronic neurological disorder caused by neurodegeneration within the central nervous system. It results in impaired physical, cognitive, and psychological functioning and can also lead to lower urinary tract symptoms including nocturia. While clinical trials have suggested an association between nocturia and melatonin secretion, to our knowledge, no qualitative research has been conducted on the experience of taking melatonin to treat nocturia in progressive MS within a clinical trial. Methods . 17 semistructured qualitative interviews were conducted as part of a double-blind, randomised, placebo controlled, crossover, clinical trial with consenting adults with MS. Interviews explored participants' experiences of nocturia associated with MS and their experience of taking melatonin as a trial treatment for nocturia versus a placebo. Data was analysed using a thematic analysis. Results . Themes on the experience of nocturia revealed participants' understandings of nocturia, the impact it had on their night, and increased daily fatigue. Themes on the intervention showed perceived improvements to nocturia, sleep, and energy and negative effects including lethargy, a lack of significant change, and physical side effects including vivid dreams. Conclusion . This qualitative exploration revealed an association between nocturia and increased levels of fatigue during the day by those with MS. However, perspectives towards the effectiveness of melatonin as a potential treatment varied as both placebo and melatonin were perceived as having very similar effects.